Anthropogenic Impact on Plankton and Benthos Assemblage in the Lagos Lagoon, Nigeria - Ugwumba Adiaha Alda Alex; Esenowo Imeh Kokoete (Croatian Journal of Fisheries, 2020)
The physico-chemical parameters, plankton and macro-benthic invertebrates of the Lagos Lagoon (Badore, Ajah), Lagos State, Nigeria were studied between February and July 2018 at four sampling stations in a disparate range of human activities and impact. The result of phytoplankton analysis indicated a total of 56 genera with 40 genera within Bacillariophyta, accounting for 72% of the abundance. Zooplankton comprised 26 genera with 82% of the abundance of crustacea. The benthic macroinvertebrates were composed of mollusca, arthropoda and annelida. Results also indicated that the main drivers affecting the abundance and distribution of planktonic and benthic invertebrates were water temperature, pH, TDS and EC. The monthly variations of physico-chemical parameters in the Lagoon could be the result of human activities associated with transportation, fishing and domestic sewage disposal from the surrounding settlements. Therefore, it is necessary that relevant authorities keep in check some of these activities around the Lagoon as well as educate the population on the necessity for the conservation of these water resources.